Espermidina diminui a atividade da enzima Na+,K+-ATPase pela via de sinalização NMDA/NOS/GMPc/PKG em hipocampo de ratos - Carvalho, Fabiano Barbosa (2011)
Spermidine (SPD) is an endogenous polyamine with polycationic structure present in the central nervous system of mammals. SPD regulates biological processes, such as Ca2+ influx by glutamatergic N-methyl-D-aspartate receptor (NMDA receptor), which has been associated with nitric oxide synthase (NOS) and cGMP/PKG pathway activation and a decrease of Na+,K+-ATPase activity in rats cerebral córtex synaptossomes. Decreased Na+,K+-ATPase activity, as well as decreased enzyme expression, directly impairs neurotransmitter signaling with deleterious consequences on learning and memory. The enzyme Na+,K+-ATPase establishes Na+ and K+ gradients across membranes of excitable cells and by this means maintains membrane potential and controls intracellular pH and volume. However, it has not been defined whether SPD modulates Na+,K+-ATPase activity in the hippocampus. In this study we investigated whether SPD alters Na+,K+-ATPase activity in slices of hippocampus from rats, and possible underlying mechanisms. Hippocampal slices and homogenates were incubated with SPD (0.05-10 μM) for 30 minutes. SPD (0.5 and 1 μM) decreased Na+,K+-ATPase activity in slices, but not in homogenates. MK-801 (100 μM), a non-competitive antagonist of NMDA receptor, arcaine (0.5 μM), an antagonist of the polyamine binding site at the NMDA receptor, and L-NAME (100 μM), a nitric oxide synthase inhibitor, prevented the inhibitory effect of SPD (0.5 μM). ODQ (10 μM), a guanylate cyclase inhibitor, and KT5823 (2 μM), a protein kinase G inhibitor, also prevented the inhibitory effect of SPD on Na+,K+-ATPase activity. SPD (0.5 and 1.0 μM) increased NO2 plus NO3 (NOx) levels in slices, MK-801 (100 μM) and arcaine (0.5 μM) prevented the effect of SPD (0.5 μM) on the NOx content. These results suggest that SPD-induced decrease of Na+,K+-ATPase activity involves NMDA/NOS/cGMP/PKG pathway.